Repercussion on the quality of life of women with cancer during the COVID-19 pandemic (Research, Society and Development, 2021)
Introduction: The social isolation caused by the COVID-19 pandemic for people who are victims of cancer, can directly affect the treatment in a negative way, as they need continuous multidisciplinary care. Thus, routine assessments were postponed, laboratory tests postponed, treatment interrupted and surgeries cancelled. However, social isolation is necessary so that there is no transmission of Sars-Cov-2. Objective: This study aimed to describe the possible repercussions that can negatively impact the quality of life of women victims of breast cancer during the COVDI-19 pandemic. Method: The study is an integrative literature review, searches were designed in all languages ​​in the databases: Virtual Health Library (VHL) and PubMed and science direct, the descriptors for the results were: ((Breast cancer)) and ((COVID-19)) and ((quality of life)). Articles from 2020-2021 were included. Results and discussion: Studies show that breast cancer is the pathological condition that most affects the emotional condition of women, as it directly reflects on the woman's femininity. Thus, the COVID-19 pandemic had even more repercussions, due to the delay in treatment, a risk that COVID-19 may reflect on their general health, leaving them more emotionally vulnerable. Conclusions: Studies have shown that the COVID-19 pandemic may result in reduced quality of life, as they are already negatively impacted, as breast cancer hurts the femininity of these women. Therefore, few studies were located on the respective theme, thus showing the need and relevance of further evidence in the future.